Social activities of non-governmental organizations in relation to families with children - R. M. Sadykov; N. L. Bolshakova; R. H. Khamadeeva (Вестник университета, 2021)
The article considers the social activities of non-governmental organizations in relation to families with children in the context of the modernization of the system of social services for the population, which is aimed at encouraging citizens to independently overcome life difficulties. The paper analyses the social activities of commercial and non-profit organizations, innovative technologies, the quality and variety of services provided to families in need. The authors determine the main barriers to their interaction with government agencies. The study notes, that social activities of commercial and non-commercial organizations expand the range of social services, their accessibility to the population, improve the quality and efficiency. The paper defines the priority directions of activities of socially oriented NGOs in relation to families and children in the context of Russian realities: assistance to families in the development and upbringing of children, assistance in employment and adaptation of mothers, social support for families in need, etc. The study established that the non-governmental sector responds quickly to the needs of citizens and acute social problems, which allows it to be an effective performer of social services. The authors conclude that in Russia it is necessary to form an effective management system for the development of non-governmental organizations as providers of services to families in need, optimize inter-sectoral collaboration. Social activities of the non-governmental sector have great potential and development prospects.